ANALYSIS OF A NEW LEARNING PARADIGM BASED ON KURIKULUM MERDEKA - Saptono Nugrohadi; Katarina Herwanti; Mujiono Mujiono; Sukma Nur Ardini; Mega Novita (Proceeding International Conference on Digital Education and Social Science, 2022)
In an effort to provide a safe and stable learning environment in the aftermath of the COVID-19 pandemic, the Indonesian Ministry of Education, Culture, Research and Technology (Kemendikburistek) has issued a policy of the Kurikulum Merdeka for all levels of education. The underlying philosophy of this initiative is the concept of Merdeka Belajar, which essentially means that students are given the freedom to explore their respective interests and talents. This policy is a transformative step for the realization of Excellent Indonesian Human Resources (HR) who have a Pancasila student profile. Merdeka Belajar has been launched for 21 episodes through the end of June 2022. As this is a relatively new policy, some are naturally skeptical. Furthermore, comprehensive discussion of why and how the Kurikulum Merdeka is implemented to date is limited. Therefore, this paper presents an analysis of the new learning paradigm seen from the Kurikulum Merdeka perspective and the creation of a systematic review of the relevant databases for the adoption of curriculum changes. There is strong evidence that the Kurikulum Merdeka is a viable way to overcome learning losses due to school closures during the COVID-19 pandemic. This work has the potential to become an important reference to increase commitment and cooperation from various parties in implementing policies for higher quality education.